2021
DOI: 10.15252/emmm.202013579
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput screening identifies suppressors of mitochondrial fragmentation in OPA1 fibroblasts

Abstract: Mutations in OPA1 cause autosomal dominant optic atrophy (DOA) as well as DOA+, a phenotype characterized by more severe neurological deficits. OPA1 deficiency causes mitochondrial fragmentation and also disrupts cristae, respiration, mitochondrial DNA (mtDNA) maintenance, and cell viability. It has not yet been established whether phenotypic severity can be modulated by genetic modifiers of OPA1. We screened the entire known mitochondrial proteome (1,531 genes) to identify genes that control mitochondrial mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 103 publications
5
45
0
Order By: Relevance
“…The therapeutic options for OPA1-related DOA are still in a very preliminary phase [ 189 ], with some encouraging results obtained by off-label idebenone administration in DOA patients [ 190 ]. At the preclinical stage numerous research pipelines are active, from screening molecules for repurposing [ 191 ], mechanistic studies to define therapeutic targets [ 192 , 193 ], and gene therapy strategies [ 194 ], including the recent gene editing of a frequent OPA1 missense mutation [ 195 ]. Clinically DOA does not have the confounder of spontaneous recovery of visual function as for LHON, but it is also a slowly progressing or substantially stable disease that questions are posed on which primary endpoint most reliably may reflects therapeutic efficacy.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic options for OPA1-related DOA are still in a very preliminary phase [ 189 ], with some encouraging results obtained by off-label idebenone administration in DOA patients [ 190 ]. At the preclinical stage numerous research pipelines are active, from screening molecules for repurposing [ 191 ], mechanistic studies to define therapeutic targets [ 192 , 193 ], and gene therapy strategies [ 194 ], including the recent gene editing of a frequent OPA1 missense mutation [ 195 ]. Clinically DOA does not have the confounder of spontaneous recovery of visual function as for LHON, but it is also a slowly progressing or substantially stable disease that questions are posed on which primary endpoint most reliably may reflects therapeutic efficacy.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…For a more detailed description of therapeutic approaches for mitochondrial optic neuropathies, we refer the reader to a comprehensive review that has been recently published [ 195 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Organelle features extracted included cell areas, expression intensity, the number of spots, roundness, length and width. We also included SER textural features which measure local patterns of pixel intensity providing the structural information of the organelle loading (reviewed here (Di Cataldo and Ficarra, 2017) (Cretin et al, 2021). We designed, trained and evaluated a Dense Neural Network by splitting the entire dataset (n = 1,560,315 identified cells) into training (40%), validation (30%) and test datasets (30%).…”
Section: Resultsmentioning
confidence: 99%
“…Morphologically defined features are included such as cell areas, expression intensity, the number of spot, roundness, length and width. SER texture features are also included defined as Spot, Hole, Edge, Ridge, Valley, Saddle, Bright and Dark which measure local patterns of pixel intensity providing the structural information of the organelle loading (reviewed here (Di Cataldo and Ficarra, 2017) (Cretin et al, 2021). b .…”
Section: Supplementary Figuresmentioning
confidence: 99%
“…Functional mitochondrial fusion mediated by L-OPA1 preserves cardiac function, and mitochondrial fragmentation may trigger dilated cardiomyopathy and heart failure ( Wai et al, 2015 ). Fresh new research found that knockout of the phosphatidyl glycerophosphate synthase PSG1 causes cardiolipin reduction, thus rescuing mitochondrial fragmentation caused by OPA1 dysfunction ( Cretin et al, 2021 ). OPA1 is another major player in maintaining the mitochondrial architecture, regulating apoptosis, and sustaining the homeostasis of mitochondrial fusion and fission.…”
Section: Significant Players Of Mitochondrial Dynamicsmentioning
confidence: 99%